Pengaruh Program Pelatihan K3 terhadap Perilaku Aman Pekerja Kontruksi - Purba, Hairum Nafsiah; Panjaitan, Wiranti Utami; Khairani, Cindy; Hasibuan, Abrurrozzaq (Melati Institute, 2025)
Occupational Safety and Health (OHS) is an important aspect in the construction industry which has a high risk of work accidents. OHS training programs are designed to increase workers' awareness and knowledge of safe work practices. This literature study aims to provide the influence of OHS training programs on changes in construction workers' safe behavior. By reviewing 15 scientific journals, it was found that OHS training significantly increased compliance with safety procedures, improved risk perception, and reduced the incidence of work accidents. These results indicate that OHS training is an effective intervention in creating a positive safety culture in the construction work environment.